2020
DOI: 10.1002/ep.13569
|View full text |Cite
|
Sign up to set email alerts
|

Integration of solar dryer with a hybrid system of gasifier‐solid oxide fuel cell/micro gas turbine: Energy, economy, and environmental analysis

Abstract: A novel approach is presented to reduce the moisture content of biomass by employing a solar dryer. The impact of decreasing moisture contents on the key parameters of the system is investigated. Also, the effect of air mass flux on drying rate of biomass is evaluated and discussed considering three alternative air mass flux rates as well as two different time periods for drying and discharging biomass, namely 15 and 30 min. Results demonstrate that moisture reduction improves the output power and efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…173 The size of the plant is also one of the major factor in order to reduce the overall installation and operation cost. 174 It is observed that increasing the plant size, the capital cost can be reduced significantly. 175 The specific cost for a PTC with 40 MW can be reduced by 28% at 160 MW, 176 and 12.1% by doubling the plant size of 50 MW.…”
Section: Techno-economic Analysismentioning
confidence: 99%
“…173 The size of the plant is also one of the major factor in order to reduce the overall installation and operation cost. 174 It is observed that increasing the plant size, the capital cost can be reduced significantly. 175 The specific cost for a PTC with 40 MW can be reduced by 28% at 160 MW, 176 and 12.1% by doubling the plant size of 50 MW.…”
Section: Techno-economic Analysismentioning
confidence: 99%
“…[ 4 ] This method can help reduce carbon dioxide emissions and prevent adverse climate change. [ 5 ] One of the various types of biomass compounds is urban waste. Waste can be defined as a solid, liquid, or gas (other than sewage) that is produced directly or indirectly from human activities and is not usable from the producer's point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, these power plants are promising in the energy‐intensive industries, especially when cooling loads demand occurs, where supplying electricity for cooling equipment is costly. Therefore, presenting innovative solutions to improve the efficiency of conventional combined power plants using advanced cycles and utilizing the recycled heat of conventional topping cycles can lead to the development of sustainable and environmentally friendly energy systems 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, presenting innovative solutions to improve the efficiency of conventional combined power plants using advanced cycles and utilizing the recycled heat of conventional topping cycles can lead to the development of sustainable and environmentally friendly energy systems. 3,4 In addition, low-temperature cycles that operate with the different working fluids are conveniently suitable for recovering heat from steam turbines in small and medium power plants in the capacity range of hundreds of kilowatts. In fact, instead of water, organic chemicals with desirable thermodynamic properties are used in these cycles so that the enthalpy drop is much lower.…”
mentioning
confidence: 99%